2020
DOI: 10.1186/s12891-019-2988-z
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of history taking, physical examination and imaging for phalangeal, metacarpal and carpal fractures: a systematic review update

Abstract: Background: The standard diagnostic work-up for hand and wrist fractures consists of history taking, physical examination and imaging if needed, but the supporting evidence for this work-up is limited. The purpose of this study was to systematically examine the diagnostic accuracy of tests for hand and wrist fractures. Methods: A systematic search for relevant studies was performed. Methodological quality was assessed and sensitivity (Se), specificity (Sp), accuracy, positive predictive value (PPV) and negativ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 76 publications
0
13
0
2
Order By: Relevance
“…It is essential to understand the clinical findings of scaphoid fractures since it could improve the sensitivity and specificity of US. Diagnosis should be focused on a deep anamnesis and a detailed physical examination, followed by diagnostic images [5,[13][14][15][16].…”
Section: Clinical Findings Of Scaphoid Fracturesmentioning
confidence: 99%
See 3 more Smart Citations
“…It is essential to understand the clinical findings of scaphoid fractures since it could improve the sensitivity and specificity of US. Diagnosis should be focused on a deep anamnesis and a detailed physical examination, followed by diagnostic images [5,[13][14][15][16].…”
Section: Clinical Findings Of Scaphoid Fracturesmentioning
confidence: 99%
“…Diagnosis is based on clinical examination and images, with wrist radiography being the most commonly used method due to its high availability and low price. Nevertheless, sensitivity and specificity of radiography in the acute phase is not optimal, presenting between 20-25 % of false negatives results, and missing close to 16 % of fractures, for which preventive immobilization, and sometimes additional images such as magnetic resonance imaging (MRI) and computed tomography (CT) are required [1][2][3][4][5]. Consequently, unnecessary wrist immobilization represents a high sanitary cost due to prolonged time off from work [6].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…When an acute scaphoid fracture is suspected conventional wrist radiographs with supplementary 3-4 special projections of the scaphoid are done. A systematic review of imaging in carpal fractures found that initial radiographs have a 43-70 % sensitivity for detecting an acute scaphoid fracture in adults [11]. Furthermore, a prospective study, where MRI was used as golden standard, showed that conventional radiographs detected 54 % of acute scaphoid fractures in children [6].…”
Section: Introductionmentioning
confidence: 99%